3D-MRI OBSTRUCTION AND VISUALIZATION OF PHARYNGEAL AIRWAY TRACT USING OPEN SOURCE SEEDED TECHNIQUE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Obstructive  Sleep  Apnea(OSA)    is  breathing  disorder  syndrome in  which  the  airway tract  pauses  during  sleep due  to  collapse  of pharyngeal  airway. It is occurred  at the  sleep time, with fourth dimensional  high resolution  in airway tract Obstruction  in children and  adults  with  OSA. Here, we  the  operator places the  seeds  that  includes  the   Oesopharyngeal  air tract  and found out  a threshold for   the  first  frame in order   to  determine the affected tissues  which   blocks   the patients pharyngeal tract. In this automated  segmentation  method it shows the  process of   MRI studies  of  the pharyngeal air pathway and  enable  diagnose of  obstructive  tissues with the collapse tissues.  Region growing method results well in Dice Coefficients compared with  manual segmentation. It  automatically  detects  90%  of  collapse  tissues.  This  approach  leads  to  segment  the pharyngeal  pathway correctly. It  uses  long  MRI scans  in order  to  diagnosis   the  collapsed  tissues  with  graph,  accurate details and coefficients  in  a  short span  of  duration.